New Approaches to Sample Preparation and Integrated Spectroscopic Methods for The Identification of Polioxyethylene Triolate Sorbitane for Pharmaceutical Examination of Drugs - Yerbolat Orazbekuly; Gulzat Aitkaliyeva; Madeniyet Yelubay (Universitas Gadjah Mada, 2020)
Due to the fast pace of development of spectroscopic research methods in the pharmaceutical expertise of drugs presented in the United States Pharmacopeia (USP) and European Pharmacopoeia (Ph. Eur.), in this paper, we examined complex methods for the identification and preparation for analysis of polyethylene sorbitan trioleate. Two new systems were identified for purification of 98% polyoxyethylene sorbitan trioleate from organic impurities in column chromatography: acetonitrile 100% and acetonitrile/acetone 7.5/2.5. It was also revealed that a chamber with metallic iodine was the most suitable for selecting an eluent and controlling the cleaning by the TLC method. Proton NMR did not detect organic impurities. Identification of polyoxyethylene sorbitan trioleate was carried out on H1, C13, COSY, and IR spectra. These research methods are characterized by simplicity in sample preparation, the availability of reagents, the effectiveness of identification and quantification analyzes, and the efficiency in labor and material costs